Repetitive Transcranial Magnetic Stimulation for Alzheimer’s Disease Based on Apolipoprotein E Genotyping: Protocol for a Randomized Controlled Study - Wei, Naili; Chen, Jian (Frontiers in Aging Neuroscience, 2021)
To date, there is a shortage of effective treatment strategies for Alzheimer's disease (AD), and although repetitive transcranial magnetic stimulation (rTMS) can improve AD cognitive function, there are obvious individual differences, which may be related to different apolipoprotein E (APOE) genotypes. As the risk and pathogenesis of AD varises greatly among different genotypes precise treatment strategies should be implemented depending upon genotype, which has not been proved by clinical studies. Apart from that, the published clinical studies are highly heterogeneous, and therefore, systematic and well-developed randomized controlled Trails (RCT) and demonstration of precise administration protocols are required. To verify this hypothesis, this project designed a RCT study, and randomly divided apoE4 carrier AD and noncarrier AD into high-frequency rTMS (HF-rTMS) or low-frequency rTMS (LF-rTMS) treatment groups. Specifically, 80 patients with AD, namely 48 APOE4 carriers and 32 non-APOE4 carriers will be included in the study. After that, based on different stimulation frequencies of rTMS, they will be divided into the HF-rTMS group and the LF-rTMS group, when patients with AD will be randomly assigned to different treatment groups. After AD patients are involved in the study, their memory, cognition, anxiety, depression and activities of daily living will be tested before and during 2 weeks of rTMS. Furthermore, peripheral blood will be collected before and after treatment to detect changes in pathological indexes via MSD platform (Meso Scale Discovery), while 32-channel EEG data will be also collected to detect and analyze changes in gamma oscillation. In addition, these patients will be followed up for 6 months and their neuropsychological scale was also evaluated every month. At present, our study has included 18 AD patients (10 APOE4 carriers; 8 noncarriers). Our study is still in progress. The grouping has not been unblinded. But the preliminary data demonstrated that noncarriers had better MoCA score improvement than APOE4 carriers. The results indicated that the two populations of AD patients should be treated differently. Thus, this project will provide direction for precision rTMS in AD and also promotes a shift in relevant treatment philosophy.